Clinical and radiological findings of silent hypoxia among COVID-19 patients. Issue 10 (October 2021) - Okuhama, Ayako; Ishikane, Masahiro; Hotta, Masatoshi; Sato, Lubna; Akiyama, Yutaro; Morioka, Shinichiro; Suzuki, Setsuko; Tajima, Tsuyoshi; Yamamoto, Makiko; Teruya, Katsuji; Izumi, Shinyu; Ohmagari, Norio
Abstract: The aim of this study was to describe the clinical and radiological findings of COVID-19 patients with "silent hypoxia, " who had no dyspnea on admission even though their oximetry saturation was less than 94%. This retrospective cohort study included all COVID-19 patients (n = 270) at a large tertiary care hospital between January 31 and August 31, 2020. Clinical and radiological characteristics of patients who met our criteria of "silent hypoxia", which included those who reported no dyspnea even though oximetry saturation was <94%, were extracted. Eight patients (3.0%) met the criteria for "silent hypoxia." The median age was 61 years (interquartile range [IQR]: 48.8–72.3), and five (62.5%) were men. All patients had consolidation on CT and showed a moderate to high COVID-19 CT severity score (median: 13.5, IQR: 10.8–15.3). The median FIO2 of the maximum oxygen required was 55 (IQR: 28–70)%. Two patients (25.0%) were intubated, and one patient (12.5%) underwent extracorporeal membrane oxygenation. Some COVID-19 patients with "silent hypoxia" may develop severe disease. Close and accurate monitoring of patients using arterial blood gas and pulse oximetry is necessary, regardless of their symptoms.